Low Systemic Inflammation Response Index Predicts Good Prognosis in Locally Advanced Pancreatic Carcinoma Patients Treated with Concurrent Chemoradiotherapy. (30th July 2020) - Topkan, Erkan; Mertsoylu, Huseyin; Kucuk, Ahmet; Besen, Ali Ayberk; Sezer, Ahmet; Sezen, Duygu; Bolukbasi, Yasemin; Selek, Ugur; Pehlivan, Berrin
Abstract : Background . We investigated the prognostic significance of pretreatment systemic inflammation response index (SIRI) in locally advanced pancreatic carcinoma (LAPC) patients treated with concurrent chemoradiotherapy (CRT). Methods . Present retrospective cohort analysis investigated consecutive 154 LAPC patients who received radical CRT. The SIRI was defined as: SIRI = neutrophil × monocyte / lymphocyte   counts . Ideal SIRI cutoff(s) influencing overall survival (OS) and progression-free survival (PFS) results were sought by using receiver operating characteristic (ROC) curve analysis. The primary endpoint was the interaction between the SIRI and OS results. Results . The median follow-up, PFS, and OS durations were 14.3 (range: 2.9-74.6), 7.9 [%95 confidence interval (CI): 5.7-10.1), and 14.7 months (%95 CI: 11.4-18.0) for the entire cohort, respectively. ROC curve analyses determined the ideal SIRI cutoff that exhibiting a significant link with OS and PFS outcomes at the rounded 1.6 point (AUC: 74.3%; sensitivity: 73.8%; specificity: 70.1%).The SIRI <1.6 patients (N = 58 ) had significantly superior median PFS (13.8 versus 6.7 months; P < 0.001 ) and OS (28.6 versus 12.6 months; P < 0.001 ) lengths than SIRI ≥1.6 patients (N = 96 ), respectively. Although the N0 (versus N1; P < 0.05 ) and CA 19-9 ≤90 U/mL (versus >90 U/mL) appeared as the other significant associates of better OS and PFS in univariate analyses, yet the results of multivariate analyses confirmed the SIRI <1.6 as the independent indicator of superior OS and PFS (P < 0.001 for each). Conclusion . Pretreatment SIRI is a novel independent prognosticator that may further enhance the conventional tumor-node-metastases staging system in a more precise prediction of the OS and PFS outcomes of LAPC patients after radical CRT.